MYTHOPOETICS OF THE POSTMODERNIST NOVEL: AT THE LEVEL OF STRUCTURAL-COMPOSITIONAL PROPERTIES - Abdullayeva Yegana Atamoglan, (International Journal of Innovative Technologies in Social Science, 2024)
The postmodernist novel is an original genre modification of the late 20th-21st century postmodernist trend in world literature, which differs in its unique content, form and functional characteristics in the metatext space. The typological specificity of the postmodernist novel, which combines universal and specific features, is characterized by a dialogue with the historical past. Postmodernist novel revives mythopoetic thought and context, archetype-plot and archetype-images become relevant in such novels, mythologems manifest themselves in the form of plot, motif or image. In the article, the interaction and unity of the archetype-plot and archetype-image division is revealed and analyzed as the poetics of the postmodernist novel. The author of the article studies the postmodernist novel as a unique type of incitement in terms of structure-composition and content, and draws the myths and mythologems involved in the text into the object of investigation.